The Effectiveness Of Therapeutic Administration Of Warm Compresses Of Ginger Against Pain Reduction With Gouty Arthritis (Gout) In Tambunan Baruara Village, Balige District, Toba Regency In 2023 - Ricard Fredrik Marpaung (LPPM Universitas Abdurrab, 2023)
ABSTRACK Gout arthritis is characterized by high levels of uric acid in the blood and repeated attacks of acute pain in the joint area. One of the nonpharmacological management of pain is to do warm compresses of ginger. Warm compresses of ginger are one of the interventions to reduce pain because the content of ginger that has a hot taste can give a warm response to areas of the body that feel pain, causing dilation of blood vessels. The purpose of this study was to determine the effectiveness of giving warm ginger compress therapy to pain reduction with gouty arthritis (gout) in the elderly in Tambunan Baruara Village, Balige District, Toba Regency. The research method used is descriptive with a case study approach of the nursing care process carried out in the management of pain clients including assessment, nursing diagnosis, nursing intervention, implementation and evaluation. The results showed that there was a change in the scale of pain before and after ginger warm compress therapy, both in the first respondent, second respondent and third respondent. Ginger warm compress therapy can reduce the scale of pain in the elderly in Tambunan Baruara Village, Balige District, Toba Regency